O ensino de Camões. Aproximações a um problema maior - Bernardes, José Augusto Cardoso (2012)
Although it remains in Secondary School Programs since a lot of decades, Camões is still not well taught. From all the problems that could be brought up, I distinguish two: the distinguish two: the splitting between the university´s investigation and the teaching and the lack of clearly defined aims, both in lyric and in epic. Because of that, it is justified to consider some changes, envolving the formation of Portuguese teachers and the ajustment of the Programs and Methods, according to the needs and the circumstancies of the students.